1996
DOI: 10.1177/026119299602400511
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Validation Study in Germany on Two in Vitro Alternatives to the Draize Eye Irritation Test, the HET-CAM Test and the 3T3 NRU Cytotoxicity Test

Abstract: During 1988–1992, a validation study was carried out in Germany on the capacity of two in vitro tests to replace the Draize eye test for severely eye irritating chemicals, namely, the hen's egg chorio-allantoic membrane (HET-CAM) test and the 3T3 cell neutral red uptake (NRU) cytotoxicity test, which had shown promising results in an earlier test development project. The formal validation study, which was coordinated by Centre for Documentation and Evaluation of Alternative Methods to Animal Experiments (ZEBET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 13 publications
2
40
0
Order By: Relevance
“…This indicates that there will also be a need for in vitro methods that can identify conjunctiva effects, and especially conjunctiva redness, to fully replace the in vivo Draize eye test if the animal data continue to be interpreted as currently expressed in UN GHS and EU CLP and the classifications obtained thereafter continue being used as reference in the evaluation/validation of alternative methods. The Hen’s Egg Test–Chorioallantoic Membrane (HET-CAM) (Luepke 1985 ; de Silva et al 1992 ; Gilleron et al 1996 ; Spielmann et al 1996 ) and similar methods like the Chorioallantoic Membrane Vascular Assay (CAMVA) (Bagley et al 1994 ) have been proposed to provide information on conjunctiva effects in vivo due to the similarity of the CAM to the conjunctiva. Both HET-CAM and CAMVA underwent multiple international validation studies (Bagley et al 1992b , 1999b ; Spielmann et al 1993 , 1996 , 1997 ; Brantom et al 1997 ; Ohno et al 1999 ; Hagino et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates that there will also be a need for in vitro methods that can identify conjunctiva effects, and especially conjunctiva redness, to fully replace the in vivo Draize eye test if the animal data continue to be interpreted as currently expressed in UN GHS and EU CLP and the classifications obtained thereafter continue being used as reference in the evaluation/validation of alternative methods. The Hen’s Egg Test–Chorioallantoic Membrane (HET-CAM) (Luepke 1985 ; de Silva et al 1992 ; Gilleron et al 1996 ; Spielmann et al 1996 ) and similar methods like the Chorioallantoic Membrane Vascular Assay (CAMVA) (Bagley et al 1994 ) have been proposed to provide information on conjunctiva effects in vivo due to the similarity of the CAM to the conjunctiva. Both HET-CAM and CAMVA underwent multiple international validation studies (Bagley et al 1992b , 1999b ; Spielmann et al 1993 , 1996 , 1997 ; Brantom et al 1997 ; Ohno et al 1999 ; Hagino et al 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Hen’s Egg Test–Chorioallantoic Membrane (HET-CAM) (Luepke 1985 ; de Silva et al 1992 ; Gilleron et al 1996 ; Spielmann et al 1996 ) and similar methods like the Chorioallantoic Membrane Vascular Assay (CAMVA) (Bagley et al 1994 ) have been proposed to provide information on conjunctiva effects in vivo due to the similarity of the CAM to the conjunctiva. Both HET-CAM and CAMVA underwent multiple international validation studies (Bagley et al 1992b , 1999b ; Spielmann et al 1993 , 1996 , 1997 ; Brantom et al 1997 ; Ohno et al 1999 ; Hagino et al 1999 ). More recently, HET-CAM was also formally validated by the Interagency Coordinating Committee on the Validation of Alternative Methods (ICCVAM) for the UN GHS classification system, but it was not considered useful at that time to be used for regulatory purposes for the evaluation of the serious eye damage/eye irritation potential of chemicals, due to the lack of sufficient data for Cat 2 chemicals (ICCVAM 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1996; Budai and Varnagy 2000) on the CAM were observed over a period of 5 min (Kalweit, Gerner, and Spielmann 1987, 1990; Sterzel et al 1990; CEC 1991; Spielmann et al 1991; Macian et al. 1996; Spielmann et al 1996; Gilleron et al 1997; Schlage, Bulles, and Kurkowsky 1999).…”
Section: Methodsmentioning
confidence: 97%
“…Two eggs for controls and three eggs for test substance were used for each assay. The reactions for hemorrhage, coagulation, (Blein et al 1991;Hagino et al 1991Hagino et al , 1993Hagino et al , 1999Bagley et al 1992;Rougier et al 1992;de Silva, Rougier, and Dossou 1992;Kojima et al 1995;Doucet, Lanvin, and Zastrow 1999), and lysis (Luepke and Kemper 1986;Sterzel et al 1990;CEC 1991;Spielmann 1995;Macian et al 1996;Gettings et al 1996;Budai and Varnagy 2000) on the CAM were observed over a period of 5 min Spielmann 1987, 1990;Sterzel et al 1990;CEC 1991;Spielmann et al 1991;Macian et al 1996;Spielmann et al 1996;Gilleron et al 1997;Schlage, Bulles, and Kurkowsky 1999).…”
Section: Test Proceduresmentioning
confidence: 99%